Specialized active leprosy search strategies in an endemic area of the Brazilian Amazon identifies a hypermutated Mycobacterium leprae strain causing primary drug resistance - Bouth, Raquel Carvalho; Gobbo, Angélica Rita; Barreto, Josafá Gonçalves; do Carmo Pinto, Pablo Diego; Bittencourt, Maraya Semblano; Frade, Marco Andrey Cipriani; Nascimento, Apolônio Carvalho; Bandeira, Sabrina Sampaio; da Costa, Patricia Fagundes; Conde, Guilherme Augusto Barros; Avanzi, Charlotte; Ribeiro-dos-Santos, Ândrea; et al. (Frontiers in Medicine, 2023)
Leprosy, an infectious disease caused by Mycobacterium leprae, remains a public health concern in endemic countries, particularly in Brazil. In this study, we conducted an active surveillance campaign in the hyperendemic city of Castanhal in the northeastern part of the state of Pará using clinical signs and symptoms combined with serological and molecular tools to diagnose new cases and to identify drug resistance of circulating M. leprae strains and their distribution in the community. We enrolled 318 individuals using three different strategies to enroll subjects for this study: i) an active survey of previously treated cases from 2006 to 2016 found in the Brazil National Notifiable Disease Information System database (n = 23) and their healthy household contacts (HHC)(n = 57); ii) an active survey of school children (SC) from two primary public schools in lowincome neighborhoods (n = 178), followed by visits to the houses of these newly diagnosed SC (n = 7) to examine their HHC (n = 34) where we diagnosed additional new cases (n = 6); iii) and those people who spontaneously presented themselves to our team or the local health center with clinical signs and/or symptoms of leprosy (n = 6) with subsequent follow-up of their HHC when the case was confirmed (n = 20) where we diagnosed two additional cases (n = 2). Anti-PGL-I positivity was highest in the new leprosy case group (52%) followed by the treated group (40.9%), HHC (40%) and lowest in SC (24.6%). Whole genome sequencing of M. leprae from biopsies of three infected individuals from one extended family revealed a hypermutated M. leprae strain with multiple mutations for drug resistance in an unusual case of primary drug resistance while the other two strains were drug sensitive. Our results indicate the continuing transmission of leprosy that includes the spread of drug resistant strains in this region.